Penerapan Bela Negara di Era Revolusi Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Syarifah Humairoh; Anggita Rahmawati Harjuan; Mutiara Saputri; Denisa Cornelia; Miftakhul Rejeqi (International Forum of Researchers and Lecturers, 2024)
This article discusses the application of national defense in civic education learning in the midst of the technological revolution. This study uses a qualitative approach with the literature review method to collect and analyze various relevant literature sources. The results of the analysis show that information and communication technology (ICT) has made a significant contribution in improving the interactivity and accessibility of civic learning. However, the challenges faced include the potential erosion of national values by the influence of globalization and individualism reinforced by technology. Solutions to address these challenges include the development of relevant curricula, training for educators in the use of technology, and the implementation of practical and contextual learning activities. This research contributes to the development of more effective and relevant learning methods to the times, and emphasizes the importance of utilizing technology to strengthen the spirit of national defense and civic awareness among the younger generation.